On Path Diagrams and the Neurophenomenal Field in Bilinguals - David William Green (Languages, 2022)
Conversation is a major site for our use of language. Each conversation elicits a distinct subjective experience: a specific and dynamic phenomenal field, and it is this field that controls our communicative actions. We cannot hope to understand the neural bases of conversation without relating these to the phenomenal field. We need a neurophenomenology of the bilingual speaker. I propose and illustrate an approach involving path diagrams together with retrospective experience sampling to capture the richness of the phenomenal field as a speaker talks through an issue of concern, and relate this process to large-scale attentional networks. The proposal offers a general approach to developing a neurophenomenology of the bilingual speaker and listener.